ANALISIS KEPENTINGAN KINERJA DI INSTALASI FARMASI RUMAH SAKIT UMUM DAERAH DR. HAULUSSY AMBON MALUKU (MENURUT PERSEPSI PELANGGAN RAWAT JALAN) - , TORIA SANGADJI, Prof. Dr. Ibnu Gholib Gandjar, DEA, Apt. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
The revolution from product-oriented pharmacy services bring to patientsoriented need an improvement to achieve patient satisfaction that will good impact also for department of pharmacy. This study aims to determine customer perceptions of service, as well as anything what the customer expected to be a priority of improvement by the Pharmacy Department of RSUD Dr. Haulussy Ambon. Sample of this research are patients who does not stay in hospital or their families when they have used the Department Pharmacy RSUD Dr. Haulussy Ambon service minimum for second time. The method of sampling is using purposive sampling method consist of 101 people. Data is collecting using SERVQUAL questioners and than analyzed using gap analysis. The result showed that correlation of expectations and performance quality service at Department pharmacy in Dr. Haulussy, Ambon is meet the expectation although several revision are needed. Each department pharmacy has a different focus dimension. The biggest gap in Department Pharmacy in general (IFRS) and pharmacy askes is responsiveness, Jamkesmas pharmacy is reliability, and for 24-hour depot pharmacy is tangible.